PENGUKURAN PROGRAM PENDAYAGUNAAN DANA ZAKAT PRODUKTIF MELALUI INDEKS PENDAYAGUNAAN ZAKAT (IPZ) PADA BAZNAS KOTA BANJARMASIN - Mairijani; Nita (Indonesian Journal of Applied Accounting and Finance, 2022)
This study aims to measure the success of the productive zakat utilization program at BAZNAS Banjarmasin using the Zakat Utilization Index (IPZ). This type of research is a descriptive method with a quantitative approach. The sampling technique used is purposive sampling. The sample in this study was a group of 22 people who came from the ZCD BAZNAS program group in Banjarmasin City. This research was conducted using a survey method through questionnaires and interviews. The analytical tool used in this study is IPZ with a calculation called the Multi-Stage Weighted Index using qualitative and quantitative analysis methods. The final result is processed using the calculation formula that has been provided with the help of the Microsoft Excel application. The results showed that the success rate of the Banjarmasin BAZNAS ZCD Program was 0.50. This shows that the utilization of productive zakat is in the poor category. Only one indicator is categorized as good enough, namely the social indicator with a value of 0.75. While the other 4 indicators are in the poor category, namely cultural indicators with a value of 0.38, economic indicators with a value of 0.36, da'wah indicators with a value of 0.50, and environmental indicators with a value of 0.44. The ZCD program at BAZNAS Banjarmasin is in the strengthening phase